Teacher education for problem-based learning: evaluation of an in-service short course targeted to science and geography school teachers - Leite, Laurinda (2013)
Putting Problem-Based Learning (PBL) into practice requires teachers to abandon the role of ‘science teller’ and to take the role of ‘learning guide’. Teachers should not be expected to undergo such a major role change on their own. Then, teachers need both to understand the philosophy underlying the PBL approach and to get some guidance on how to put it into practice into their own classrooms. This paper aims at analysing 37 Science and Geography teachers’ reactions towards an in-service PBL course aiming at preparing them to put PBL into practice into their 7th to 9th grade classrooms. Data collected by means of a questionnaire show that participants were happy with the course but they would like to have been allowed to spend more time on some of the activities. In addition, some of them stated that they would like to take a follow up course and to get support when putting PBL into practice.